RENOVATION OF PUBLIC LIGHTING IN THE MUNICIPALITY OF KRŠKO: EXPERIENCES AND PLANS - Hrženjak, Darko; Pirc, Slavko; Somrak, Vanja (Journal of Energy Technology, 2024)
Public lighting is one of the areas in which it is possible to achieve significant energy savings, as well as reducing light pollution and CO 2 emissions. The company Kostak d.d. has, as a concessionary for public lighting maintenance in the municipality of Krško, prepared a project for the renovation of public lighting in accordance with the new regulation on maximum light pollution. To this end, a detailed review and inventory of all the public lighting in Krško was made. This was the basis for a later energy review of public lighting. Energy accounting was implemented to control energy consumption. In the framework of these preparations, a few new projects were started to analyse both the market of classic lamp and lumenaire producers and the market of lamp and lumenaire producers that comply with parameters defined in the new regulation. The main focus was on a market analysis of LED technologies and LED lamps for street lighting. To this end, we set up a test street to test the LED lamps and lumenaires. The result of the energy review has shown that by only replacing traditional lamps with LED technology we will not achieve the level of energy consumption required by new regulations. Therefore, we started research in the field of systems for luminous flux control and remote control of public lighting.